Stresses in lithium disilicate crowns and zirconia implants in patients with bruxism: An in silico study (Research, Society and Development, 2021)
The aim of this study was to analyze by finite element analysis the influence of the use occlusal splints in rehabilitation with zirconia implant under oblique and vertical masticatory loads. Four models were developed to simulate a clinical of absence of a premolar (element 45) replaced by zirconia implant and lithium disilicate crown. Four groups were created, SP-V without occlusal splint and vertical load; CP-V with occlusal splint and vertical load; SP-O without occlusal splint and oblique load; CP-O with occlusal splint and oblique load. The four models were built using a software (SolidWorks, SolidWorks Corporation). A load of 300N to 45º (oblique) and 90º (vertical) applied to the long axis of the whole structure. The maximum principal stress (tensile) and minimum principal stress (compression), as well as the total deformation in the implant, occlusal splint, crown and bone tissue were evaluated quantitatively and qualitatively. The CP-V and CP-O groups presented the lowest stress intensities, which were homogeneously distributed in all structures analyzed. On other hand, SP-V and SP-O groups presented highest stress distributed in a heterogeneous way. Groups with occlusal splint (CP-V and CP-O) also showed lower deformation than groups without occlusal splint (SP-V and SP-O). It´s concluded the use of occlusal splint minimizes the stresses and deformation promoted by oblique and vertical occlusal loads of up 300N in implanted lithium disilicate crown supported by zirconia implants.